5′-untranslated region sequences enhance plasmid-based protein production in Sulfolobus acidocaldarius - Kuschmierz, Laura; Wagner, Alexander; Schmerling, Christian; Busche, Tobias; Kalinowski, Jörn; Bräsen, Christopher; Siebers, Bettina (Frontiers in Microbiology, 2024)
Sulfolobus acidocaldarius, a thermoacidophilic archaeon of the phylum Thermoproteota (former Crenarchaeota), is a widely used model organism for gene deletion studies and recombinant protein production. Previous research has demonstrated the efficacy of the saci_2122 promoter (Para), providing low basal activity and high pentose-dependent induction. However, the available expression vector does not include a 5′-terminal untranslated region (5’-UTR), a typical element found in bacterial expression vectors that usually enhances protein production in bacteria. To establish S. acidocaldarius as a production strain in biotechnology in the long term, it is intrinsically relevant to optimize its tools and capacities to increase production efficiencies. Here we show that protein production is increased by the integration of S. acidocaldarius 5’-UTRs into Para expression plasmids. Using the esterase Saci_1116 as a reporter protein, we observed a four-fold increase in soluble and active protein yield upon insertion of the saci_1322 (alba) 5’-UTR. Screening of four additional 5’-UTRs from other highly abundant proteins (thα, slaA, slaB, saci_0330) revealed a consistent enhancement in target protein production. Additionally, site-directed mutagenesis of the Shine-Dalgarno (SD) motif within the alba 5’-UTR revealed its significance for protein synthesis. Ultimately, the alba 5’-UTR optimized expression vector improved the expression of various proteins, including six glycosyltransferases and one hydroxyacyl-CoA dehydratase from S. acidocaldarius, and a malto-oligosyltrehalose trehalohydrolase from Saccharolobus solfataricus, demonstrating its applicability. Our results show that the integration of SD-motif containing 5’-UTRs significantly enhanced plasmid-based protein production in S. acidocaldarius. This advancement in recombinant expression not only broadens the utility of S. acidocaldarius as an archaeal expression platform but also marks an important step toward potential biotechnological applications.